PHYSICAL ACTIVITY AND SPORT IN INCLUSIVE ENVIRONMENTS AS PROMOTERS OF POSITIVE ATTITUDES TOWARDS PEOPLE WITH DISABILITIES - Mouliaá, Luis Rodríguez de Vera; Mahique, Jeremias Deolinda; Mabota, Inês Agostinho (Seven Editora, 2025)
This article discusses the stigma and discrimination faced by people with disabilities, despite them representing more than one billion individuals worldwide. This marginalization is often sustained by unconscious biases rooted in cultural norms and outdated deficit-centered models. The literature shows that negative societal attitudes constitute one of the greatest barriers to the full inclusion of these individuals. In this context, the practice of Physical Activity and Sport (PAS) emerges as a promising means to promote positive attitudes and facilitate social inclusion. Strategies such as structured direct contact, information dissemination, and mutual cooperation in inclusive environments prove effective in reducing stereotypes and prejudices. PAS, when well-planned, can generate significant social outcomes by fostering support networks, active participation, and social skills among people with and without disabilities.DOI: https://doi.org/10.56238/sevened2025.018-018